PREDECESSORS, YIELD AND QUALITY OF WINTER WHEAT GRAIN IN THE CONDITIONS OF A FOOTHILL PART OF KABARDINO-BALKARIA - Kh. A. Malkanduev; A. Kh. Malkandueva; R. I. Shamurzaev; R. A. Gazheva (Зерновое хозяйство России)
The priority of grain use is usually determined by its great social significance which allows solving the task of food supply, especially with bread. Winter wheat as a main food crop takes up 38,6% in grain production of KBR and has a major effect on the development of agriculture. At the same time a share of qualitative food wheat remains rather small in a bulk of grain production, that’s why it’s essential to increase total amount of grain, paying special attention to quality increase. In the article we consider the effect of predecessors on productivity and quality of different winter common wheat varieties in the climatic conditions of a foothill part of Kabardino-Balkaria. We consider the study of the problem to be of current interest, knowing that winter wheat is more demanding to predecessors than the other crops and a proper choice of the best ones for a definite soil-climatic zone promotes an increase of grain productivity and quality on 5-10%. The article gives the comparative analysis of qualitative properties of winter wheat varieties after some main predecessors, i.e. maize for grain, maize for silage, sunflower and peas. The study has determined the best predecessors and their effect on yield and grain quality of new varieties in the conditions of a definite climatic zone; a possibility to use new winter wheat varieties after the best predecessors with sufficient moisture has been revealed and substantiated.  The study showed that a change of qualitative features of grain depends on biological properties of the varieties and their predecessors. The results of the research showed that the varieties reveal their best harvesting features after the best predecessors and under favorable conditions.  The research, made under conditions of vertical zone of Kabardino-Balkaria showed that the best predecessors for winter wheat are peas and maize for silage. The results of the study will be interesting for the professionals of plant-growing.